12‐2: High‐Performance OLED Microdisplays Made with Multi‐Stack OLED Formulations. Issue 1 (25th September 2020) - Hamer, John; Kondakova, Marina; Spindler, Jeffrey; Cupello, Robert; Hamer, Suzannah; Andre, Michael; McClurg, Scott; Pleten, Anatole; Primerano, Bruno; Scott, David; Scherer, George; Stickel, Scott
Abstract : High‐performance OLED microdisplays have been developed using multi‐stack white OLED architectures for high brightness and long lifetime. This approach also provides additional degrees of design freedom which can be used to reduce power, balance sub‐pixel currents, and increase color gamut. Examples with 3, 4, and 5 stacks are shown.